Exempla im Kontext. Untersuchungen zur Sammelhandschrift Berlin, Staatsbibliothek, mgf 863 aus dem Strassburger Reuerinnenkloster - Studer, M (2012)
The manuscript Berlin, SBB-PK, mgf 863 was written in about 1430 to 1435 and contains more than 600 short narrative texts in German prose (with some Latin insertions). Among them is the collection of the ›Alemannische Vitaspatrum‹ as well as an additional, extensive and multifarious exempla corpus, which mostly contains translations from well-known Latin collections such as – for example and most prominently – Caesarius' of Heisterbach ›Dialogus miraculorum‹. Because of the specific composition of the corpus and its large extent, mgf 863 builds an excellent basis for the investigation of exempla, a text type which has not received much attention in German studies. The manuscript was probably produced in Strasbourg where it belonged to the library of the nuns from the convent of St Mary Magdalen. It contains a large quantity of textual material with close links to Strasbourg in terms of content or history of transmission. My primary interest is in the texts in the manuscript, in their contents and interdependencies, as well as in their history and their contextualization in, for example, groups of manuscripts, exempla tradition and religious practice. The project aims at a contribution to exempla research as well as to literary and religious life in Strasbourg in the late Middle Ages. My approach comes primarily from literary studies, but also uses palaeographical, textualcritical, and historical methods. The thesis combines case studies of the transmission of individual exempla or groups of exempla with general research into the history of texts (›Textgeschichte‹) and the history of transmission (›Überlieferungsgeschichte‹) of German prose exempla. A repertory in the appendix provides an overview of the manuscript's content. It helps to orientate within the study; furthermore, with over 600 entries, it provides a tool for the identification of German exempla.